Effect of isovalent substitution and Quenching on the Transition Temperature of (Bi1-xPbx)2(Sr1-yBay)2Ca2Cu3O10+δ - AL-Shakarchi, E. KH. (Iraqi Journal of Physics, 2009)
A high Tc superconductor with a nominal composition(Bi1-xPbx)2(Sr1-yBay)2Ca2Cu3O10+δ for (0 £ x £ 0.5) and (0 £ y £ 0.5) was prepared bya solid state reaction method. The effect of the substitution of Pb for Bi and Ba for Sr andquenching temperature on the superconductivity has been investigated to obtain theoptimum conditions for the formation and stabilization of the high Tc phase (2223).The results showed that the optimum sintering temperature for the pure composition isequal to 875°C and the sintering time is equal to 240h with heating and cooling rate of60°C/h . Our results indicated that a small amount of (Ba = 0.1) could raise the transitiontemperature (Tc), but enhancing Ba to 0.4 has raised the resistivity and the behavior of thecomposition converted to semiconductor and ultimately for the composition that has (x =0.4, y = 0.5) was an insulator. The best value of (Tc = 122 K) is for the composition thathas x = 0.2, y = 0.1.On the other side for Ba free samples increasing of lead content up to0.3 has rise the transition temperature (Tc = 116 K) but more increases to (0.4, 0.5) causesa decrease in Tc.The effect of quenching temperature Tq on the transition temperature Tc of the (Bi1-xPbx)2(Sr1-yBay)2Ca2Cu3O10+δ was also investigated .